Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Untuk Berkarir Sebagai Akuntan Syariah (Studi Kasus Mahasiswa S1 Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Dharma Andalas) - Nofri Anita; Ingra Sovita (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of sharia knowledge, work environment, and labor market considerations on the interest of accounting students at Universitas Dharma Andalas in pursuing a career as sharia accountants. Using a quantitative descriptive approach, the research population consisted of 136 students from the 2022–2023 cohorts, with a sample of 115 respondents selected via purposive sampling. Primary data were collected through Likert-scale questionnaires and analyzed using multiple linear regression and classical assumption tests. Partial test results indicate that sharia knowledge has a significant positive effect (t = 2.148; sig = 0.034), work environment has a significant positive effect (t = 2.850; sig = 0.005), and labor market considerations have a significant positive effect (t = 3.823; sig < 0.001). An Adjusted value of 0.810 demonstrates that the model possesses strong explanatory power, with the independent variables accounting for 81% of the variation in career interest. In conclusion, sharia knowledge, work environment, and labor market considerations consistently drive students' interest in sharia accounting careers.